Carbon-coated mesoporous silica-supported Ni nanocomposite catalyst for efficient hydrogen production via steam reforming of toluene. (1st September 2020) - Xu, Haiyang; Shen, Zhangfeng; Chen, Gang; Yin, Chaochuang; Liu, Yanan; Ge, Zhigang; Wang, Yangang; Zheng, Zheng; Li, Xi
Graphical abstract: Carbon-coated mesoporous-silica supported Ni nanocomposite is an efficient catalyst for sustainable hydrogen production from steam reforming of biomass tar. Highlights: Carbon-coated mesoporous silica-supported Ni was prepared by a one-pot method. Small Ni nanoparticles were uniformly embedded in the mesoporous silica wall. Ni was stabilized owing to enhanced metal-support interaction and carbon coating. Coking, sintering and steam corrosion were suppressed due to the unique structure. The Ni-SiO2 @C exhibits a high toluene conversion and good hydrothermal stability. Abstract: Catalytic steam reforming of biomass tars is a promising technique for H2 -rich gas production. However, the undesired deactivation of nickel-based catalysts due to nanoparticle (NP) sintering and carbon deposition remains a challenge for industrial applications. In this study, we prepared a carbon-coated ordered mesoporous silica-supported Ni-based catalyst (Ni-SiO2 @C) via an evaporation-induced self-assembly (EISA) and calcination process. Characterizations revealed that the Ni-SiO2 @C has a regular mesostructure with graphitic carbon layers protected Ni NPs (average 5.5 nm in diameter) highly dispersed and embedded into the silica wall of mesoporous channels. Compared to the SBA-15 and activated carbon-supported catalysts (NiO/SBA-15 and Ni/AC), the Ni-SiO2 @C exhibits a higher toluene (a biomass tar model compound) conversion efficiency of 99.9% at 550 °C with an excellent stability for at least 46 h during steam reforming. The good performance can be attributed to the improved Ni NP dispersion, electron transfer and hydrothermal stability by enhanced metal-support interaction (MSI) as well as carbon coating. This work provides a cost-effective and easy handling approach for the synthesis of anti-sintering and coke-resistant tar reforming catalysts.